Nasogastric tube insertion using airway tube exchanger in anesthetized and intubated patients - Kim, Hyae-Jin; Lee, Hyeon Jeong; Cho, Hyun-Jun; Kim, Hae-Kyu; Cho, Ah-Reum; Oh, Narae (Korean journal of anesthesiology, 2016)
A nasogastric tube (NGT) is commonly inserted into patients undergoing abdominal surgery to decompress the stomach during or after surgery. However, for anatomic reasons, the insertion of NGTs into anesthetized and intubated patients may be challenging. We hypothesized that the use of a tube exchanger for NGT insertion could increase the success rate and reduce complications. One hundred adult patients, aged 20-70 years, who were scheduled for gastrointestinal surgeries with general anesthesia and NGT insertion were enrolled in our study. The patients were randomly allocated to the tube-exchanger group or the control group. The number of attempts, the time required for successful NGT insertion, and the complications were noted for each patient. In the tube-exchanger group, the success rate of NGT insertion on the first attempt was 92%, which is significantly higher than 68%, the rate in the control group (P = 0.007). The time required for successful NGT insertion in the tube-exchanger group was 18.5 ± 8.2 seconds, which is significantly shorter than the control group, 75.1 ± 9.8 seconds (P < 0.001). Complications such as laryngeal bleeding and the kinking and knotting of the NGT occurred less often in the tube-exchanger group. There were many advantages in using a tube-exchanger as a guide to inserting NGTs in anesthetized and intubated patients. Compared to the conventional technique, the use of a tube-exchanger resulted in a higher the success rate of insertion on the first attempt, a shorter procedure time, and fewer complications.